Cognitive Enhancer Effects of Low Memantine Doses Are Facilitated by an Alpha7 Nicotinic Acetylcholine Receptor Agonist in Scopolamine-Induced Amnesia in Rats - Bali, Zsolt Kristóf; Bruszt, Nóra; Tadepalli, Sai Ambika; Csurgyók, Roland; Nagy, Lili Veronika; Tompa, Márton; Hernádi, István (Frontiers in Pharmacology, 2019)
Alpha7 nicotinic acetylcholine receptors (nAChRs) play an important role in learning and memory and are promising targets for pharmacological cognitive enhancement. Memantine, an approved substance for Alzheimer’s disease treatment, is an antagonist of the N-Methyl-D-aspartate receptor (NMDAR) and also acts as an alpha7 nAChR antagonist. Here, we tested the interaction between an alpha7 nAChR agonist (PHA-543613) and memantine. Efficacy of memantine, PHA-543613, and their co-administration were investigated on the spatial working memory of rats using the spontaneous alternation paradigm in T-maze. Scopolamine-induced transient amnesia was used to model cognitive impairment. First, the dose-response relationship was assessed for memantine, and its lowest effective dose was found to be 0.1 mg/kg. Then, co-administration treatments with subeffective doses of the alpha7 nAChR agonist PHA-543613 and different doses of memantine were tested. The co-administration of subeffective drug doses significantly improved memory performance of the rats and reversed scopolamine-induced deficits. Interestingly, a higher than effective (0.3 mg/kg) dose of memantine did not increase performance in monotreatment, but in co-administration with PHA-543613. However, the co-administration of PHA-543613 did not further increase the efficacy of the previously effective monotreatment doses of memantine. Thus, the efficacy of memantine monotreatment and its co-administration with PHA-543613 converged to create a common ceiling effect, with an additive interaction found in the behavioral effects. These results suggest that memantine and PHA-543613 may exert their cognitive enhancer effects on the same target, possibly on the alpha7 nAChRs. Results also suggest possible benefits of a combination therapy with memantine and alpha7 nAChR agonists.